Using ontology to enhance decision-making for product sustainability in smart manufacturing - Mohammed, Moseed Abdullah Yahia; Awanis, Romli; Rozlina, Mohamed (Institute of Electrical and Electronics Engineers Inc., 2021)
Smart manufacturing is widely focused on sustainable development at the industrial level. The lack of knowledge about using smart manufacturing limits the ability to assess, share, and reuse knowledge by decision makers. The goal is to enable decision-makers to use sustainable information relevant to life cycle sustainability assessment techniques based on ontology at the design stage by facilitating the assessment, sharing, and reusing of knowledge. In this paper, we present the materials and process selection tools by illustrating their application to promoting reusability in manufacturing. It is expected that this study will contribute to solving the problem of the lack of information sharing and providing high quality and comprehensive recommendations for supporting the processes of smart manufacturing.